MODERN METHODS FOR BUSINESS EVALUATION - Tatiana N. Cheprakova; Natalia A. Rumachik; Hayk A. Engibaryan (Вестник Северо-Кавказского федерального университета, 2022)
The item dwells on studying strategies for a company value management as well as detecting factors that may have a serious impact on the value development.